Food Subsidies in General Equilibrium - Albert Jan Hummel; Vinzenz Ziesemer (Center for Economic Studies and ifo Institute (CESifo), 2021)
The Atkinson-Stiglitz theorem on uniform consumption taxation breaks down if prices are endogenous. This paper investigates the implications for optimal food subsidies in China. To do so, we build a general equilibrium model where low-skilled workers have a comparative advantage in the production of food. Food subsidies raise the relative demand for low-skilled workers, which reduces the skill premium and indirectly redistributes income from high-skilled to low-skilled workers. We calibrate our model to match key moments from the Chinese economy, including sectoral production and spending patterns that we obtain from micro-level survey data. Our results suggest that general equilibrium effects rationalize food subsidies in the range 5%-12%.
Keywords: E64; H21; Q18; 330; uniform consumption taxes; general equilibrium effects; food subsidies